Experimental two way quantum key distribution with weak+vacuum decoy state - Abdul Khir, Mohd Fared; Mohd Zain, Mohd Norzaliman; Iskandar, Bahari; Soekardjo, Suryadi; Saari, Sahbudin (Institute Mathematical Sciences, Universiti Putra Malaysia, 2013)
We report a free space based experimental demonstration of a two way Quantum Key Distribution protocol with weak+vacuum decoy state. By utilizing a different key rate formula a better maximum secure distance closer to the theoretical infinite was achieved.